Comparison of physical activity and sports engagement between children with ADHD undergoing pharmacotherapy and healthy peers - Sebastian Ludyga; Rahel Leuenberger; Fabienne Bruggisser; Uwe Pühse; Markus Gerber; Clemens Keutler; Mark Brotzmann; Peter Weber (Hogrefe AG, 2023)
Abstract: Background: Children with Attention Deficit Hyperactivity Disorder (ADHD) often face problems in the engagement and adherence of health-promoting behaviors, such as physical activity and sports. Stimulant treatment is effective for managing core symptoms, but it remains unclear if this type of treatment also normalizes the engagement in health-promoting behavior. In this case-control study, we aim to compare physical activity and sports participation between children with ADHD and healthy peers. Motor skills and aerobic fitness are investigated as potential mediators of differences between groups. Methods: Children with ADHD were matched to healthy peers based on sex, age, and socioeconomic status. Participants (N=120; age: 10.8±1.4) reported their physical activity and sports participation using a 7-day recall protocol. Their engagement in activities at moderate and vigorous intensity as well as participation in individual and team sports was derived from the protocol. Participants further completed the Movement Assessment Battery for Children-2 (MABC-2) and a submaximal test on a cycling ergometer (PWC170). Results: Children with ADHD showed lower vigorous physical activity and participation in individual sports than healthy peers. They also achieved lower scores on the MABC-2 and the PWC170. Based on path-analyses, low PWC170 partially mediated the ADHD-related fewer engagement in vigorous physical activity and individual sports. Conclusion: Children with ADHD undergoing stimulant treatment show less participation in vigorous physical activity and individual sports than healthy peers. Poor aerobic fitness partly contributes to the relation between ADHD and low physical activity.